THE INDONESIA GO PUBLIC COMPANIES INVESTMENT DECISION ON FIXED ASSETS DETERMINATION - Gesti Memarista (Accounting Study Program, Universitas Ciputra Surabaya, 2022)
Investment is one of the most crucial decisions for go public firms. By investing, the company is allocating funds for a better future. The investment will make allow the money to grow for earning a higher rate of return. This study investigates the factors that influence public companies in Indonesia in making investment decisions by choosing fixed assets. The research samples are listed manufacturing companies in the Indonesia Stock Exchange between 2015-2020. Three independent variables are used, which are operating cash flow, firm value, and firm size, while the dependent variable is investment. The analysis technique used is multiple linear regression. The study result shows that Indonesia’s go- public companies’ investment decision on fixed assets has significantly been determined by operating cash flow and firm size. Meanwhile, firm value has no significant effect on investment decisions.